Career adaptability and job burnout of pediatric residents: the role of psychological resilience and insomnia - Jie Cao; Guixin Lu; Li Gan; Yuanan Nie; Zhihui Liu; Zongxuan Feng; Zikai Xu; Xi Yu; Oudong Xia (Medical Education Online, 2025)
Background Pediatric residents face significant occupational stress due to the demanding work environment, which often leads to high levels of job burnout. The study examined the internal mechanisms by which career adaptability could influence job burnout, focusing on the mediating role of psychological resilience and the moderating effect of insomnia.Methods A cross-sectional survey was conducted from March to May, 2024, among 866 pediatric residents in the Pearl River Delta region, using a convenience sampling. The sample consisted of pediatric residents with standardized residency training: 299 (34.53%) first-year, 291 (33.60%) second-year, and 276 (31.87%) third-year. The majority of pediatric residents were females (529, 61.09%), and the remaining were males (337, 38.91%). The participants completed the Career Adapt-Abilities Scale (CAAS), the Maslach Burnout Inventory-General Survey (MBI-GS), the Connor-Davidson Resilience Scale (CD-RISC), and the Insomnia Severity Index (ISI). The moderated mediation model was used for the statistical analysis.Results The findings indicated that career adaptability was negatively correlated to job burnout among pediatric residents (β = −0.788, p < 0.001). Psychological resilience was identified as a partial mediator of the relationship, which enhanced the protective effects of career adaptability, accounting for 23.89% of the total effect. However, insomnia was identified as a moderator of the pathway, weakening the beneficial impact of psychological resilience (β = −0.016, p < 0.001). Therefore, pediatric residents with high level of insomnia were more susceptible to job burnout, even when they exhibited strong career adaptability and psychological resilience, which underscored the detrimental role of sleep disturbance.Conclusion The results showed the importance of addressing sleep disorder to mitigate job burnout among pediatric residents. Comprehensive interventions should include structured career planning, social support system, resilience training, and sleep management programs, with the objective of fostering the well-being and professional satisfaction of pediatric residents, which in turn should lead to improvement in healthcare outcomes.